Pluralism And Freedom Of Religion In Indonesia In Context Of The Religious Blasphemy Prevention Act - Johannes Johny Koynja (Faculty of Law, University of Mataram, 2018)
The point of the problem spectrum that becomes the legal issue in this article is in the establishment of the Act Number 1/PNPS/1965 on Prevention of Abuse and/or Blasphemy to the Religion as requested its examination to the Constitutional Court. The Constitutional Court of the Republic of Indonesia in its decision assess that the Applicant, in fact, wishes only to look for interpretation and form